Proposal and comprehensive thermodynamic performance analysis of a new geothermal combined cooling, heating and power system. Issue 1 (31st December 2022) - Wang, Yang; Yang, Li; Ma, Tingshuang; Yu, Xiaobing; Ju, Wenping; Huang, Jiasi; Yan, Fei
Abstract: This study proposes a new combined cooling, heating and power (CCHP) system applied for geothermal energy. In the proposed system, a water heater is introduced to utilize the exhaust geothermal water for supplying heating, and the throttled valve of the basic flash cycle is replaced by an ejector for cooling output. To evaluate the system performance, detailed mathematic models are established and validated. Based on the basic condition (170°C geothermal water), the exergy efficiency of the proposed system is 44.34% and the sum of the power, cooling output and heating output is 10, 283.68 kW. Also, the exergy loss analysis demonstrates that the component of the water heater, ejector, turbine, condenser and flasher has a large improved space to reduce the exergy destructions for system performance enhancement. At last, the parametric analysis results suggest that there exists an optimal flash pressure (around 140 kPa) to maximize the exergy efficiency. Within the discussed ranges, both the increase of the outlet temperature of water heater and condenser temperature will damage the system exergy efficiency, while a higher evaporator temperature is beneficial for the system exergy efficiency.